Peer Group and Text Message–Based Weight-Loss and Management Intervention for African American Women. (August 2018) - Lee, Sohye; Schorr, Erica; Chi, Chih-Lin; Treat-Jacobson, Diane; Mathiason, Michelle A.; Lindquist, Ruth
About 80% of African American (AA) women are overweight or obese. Accessible and effective weight management programs targeting weight loss, weight maintenance and the prevention of weight regain are needed to improve health of AA women. A feasibility study was conducted to examine the feasibility, acceptability, and potential efficacy of a 16-week intervention protocol for weight loss and management that combined daily text messages and biweekly peer group sessions. Modest but statistically significant reductions were detected in weight and body mass index from baseline to 16 weeks. At baseline, 36% of participants were in action and maintenance stages in measures of the stages of change for weight loss and management; this percent increased to 82% at 16 weeks. Findings of this feasibility study provide preliminary evidence of an educational intervention that could motivate women and lead to successful behavior change, and successful weight loss and management for AA women.